1966
DOI: 10.1115/1.3645962
|View full text |Cite
|
Sign up to set email alerts
|

Low Cycle Fatigue Crack Propagation Characteristics of High Strength Steels

Abstract: The findings in this report are not to be construed as an official Departnent of the Amy position unless so designated by other authorised documents. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The crack growth behaviour seems similar to the wrought material after heat treatment [wrought material data taken from Bathias and Pelloux (1973) and Carman and Katlin (1966)]. However, previous studies on SLM-produced materials, in particular on Ti-6Al-4V, have indicated that porosity significantly reduces the fatigue strength (Brandl et al , 2012; Leuders et al , 2013).…”
Section: Resultsmentioning
confidence: 72%
“…The crack growth behaviour seems similar to the wrought material after heat treatment [wrought material data taken from Bathias and Pelloux (1973) and Carman and Katlin (1966)]. However, previous studies on SLM-produced materials, in particular on Ti-6Al-4V, have indicated that porosity significantly reduces the fatigue strength (Brandl et al , 2012; Leuders et al , 2013).…”
Section: Resultsmentioning
confidence: 72%
“…In the diagram, h is identified both with the in-plane dimension of specimen width W (closed symbols) and with the out-of-plane specimen thickness B (open symbols). Data are taken from the compilation in Ritchie and Knott (1973), derived from the experimental fatigue-crack growth results for low to ultrahigh strength steels at ambient temperatures at R ∼ 0 in Carman and Katlin (1966), Wei et al (1967), Crooker et al (1968), Miller (1968, Bates et al (1969), Crooker and Lange (1970), Clark and Wessel (1970), Evans et al (1971), Ritchie and Knott (1973).…”
Section: Physical Interpretationmentioning
confidence: 99%
“…To facilitate this approach, we use the compilation of ambient-temperature data from the work of Ritchie and Knott (1973), based on experimental fatigue-crack propagation studies at ambient temperatures on a wide range of steels from (Carman and Katlin, 1966;Wei et al, 1967;Crooker et al, 1968;Miller, 1968;Bates et al, 1969;Crooker and Lange, 1970;Clark and Wessel, 1970;Evans et al, 1971;Ritchie and Knott, 1973). This collection of data represents steels with almost a fivefold variation in yield strength, from 433 to 2035 MPa, and includes several Ni-Cr low alloy steels (4340, En24, En30A, D6Ac), a 9Ni-4Co steel, NiMo-V rotor steel, an H-11 tool steel, and a series of ultrahigh strength Ni-maraging steels.…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
“…Detection of initial crack extension was made by a beam-type displacement gage instrument with a strain gage circuit, also shown in Fig. Al. The plane-strain fracture toughness data, obtained at room temperature, for the 9Ni-4Co-0.25C steel under investigation appears in Table Al Among the criteria used to determine the validity of the K Ic values was the requirement that the specimen thickness equal at least 2.5 times the plane-stress plastic zone size 2r y , where 2r y = (l/7r)(K/a YS ) 2 .t The K Ic values reported in Table Al …”
Section: Fracture Toughness Testsmentioning
confidence: 99%
“…The usefulness of employing the fracture mechanics stress-intensity factor (K) in analyzing the growth rate of fatigue cracks in high-strength structural metals is well documented (1)(2)(3)(4). This procedure offers the opportunity to correlate subcritical flaw growth characteristics directly with the fracture mechanics failure parameter, plane strain fracture toughness (K Ic ).…”
Section: Introductionmentioning
confidence: 99%